Classification Of Welfare Of Rw 006 Kalideres Village Using The Naïve Bayes Method - Adella Fitriany Cahyana; Veri Arinal (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The welfare level is a measurement of whether people or citizens in a country can achieve a decent quality of life or not. We can still see social things that happened before us which result in the absence of justice and position in society. As happened in Kalideres Village RW 006, the level of welfare still occurs when social assistance is provided, both from the government and donors who want to help. This research uses the Nave Bayes algorithm method to classify welfare. hoped that it could help the government and donors so that the donations that will be given can be accepted by the people entitled to them. The results of the Naïve Bayes classification get an accuracy value of 85%, where the precision value of the non-prosperous data is 97%, the prosperous data is 73%, for the recall value of the non-prosperous data is 80%, and the prosperous data is 95%.